Performance evaluation of some infiltration equations in Aljabal Alakhdar, Libya - Abdelatty, Osama A.; Momen, Mohamed A. (Al-Mukhtar Journal of Sciences, 2016)
This study was conducted to evaluate the performance of some infiltration rate models. Four Models, was chosen, Kostaikov model (KO), Modified Kostiakov model (MK), Philip model (PH) and Horton model (HO). Infiltration rate has been measured by using the double-ring infiltrometer. Eighteen infiltration tests were conducted according to the soil texture in the field. The parameters of each model were obtained by the best-fit techniquewith field data. We compared measured and calculated infiltration rate by these models. The results of this study showed that the four models were performed well to describe the filtration rate of the study area. Where the values of (RMSE) were 2.06, 2.69, 5.38, 6.13 (mm/hr) and corresponding values of (R2) were 0.96, 0.94, 0.87, 0.88 to Philip model, Kostiakov model, Horton model and Modified Kostiakov model respectively.